Osseointegrated Implant Fracture: Causes and Treatment - Gealh, Walter Cristiano [UNESP]; Mazzo, Valeria; Barbi, Francisco; Camarini, Edevaldo Tadeu (Allen Press Inc, 2011)
Despite its high success rate, therapy with osseointegrated dental implants is not free of complications. Among the problems that may occur is fracture of implants, which, albeit a rare phenomenon, may lead to unpleasant clinical outcomes for the patient, as well as for the clinician. Thus, it is paramount to know the factors related to the biological processes involved in maintenance of osseointegration and biomechanics applied to dental implants to prevent such complications, as well as treatment options available to deal with the problem. Therefore, the objectives of this work were to investigate the literature to identify causative factors that may lead to fracture of dental implants and to discuss available procedures.
Keywords: implant fracture; bone resorption; occlusal loads; parafunctional forces; metal fatigue